Association between Maternal Neuraxial Analgesia and Neonatal Outcomes in Very Preterm Infants - Liu, Lilly Y.; Lange, Elizabeth M. S.; Yee, Lynn M. (American Journal of Perinatology Reports, 2023)
Background Although the use of neuraxial analgesia has been shown to improve uteroplacental blood flow and maternal and fetal hemodynamics related to labor pain, possibly improving immediate outcomes in term neonates, the association between neuraxial analgesia use and outcomes in preterm neonates remains unclear.Objective The aim of this article was to evaluate the association between maternal use of neuraxial analgesia and neonatal outcomes in very preterm infants.Methods This is a retrospective cohort study of women delivering singleton neonates between 23 and 32 weeks' gestation at a large academic center between 2012 and 2016. Outcomes of neonates born to women who used neuraxial analgesia for labor and/or delivery were compared to those whose mothers did not. Multivariable logistic regression was utilized to assess the independent associations of neuraxial analgesia use with neonatal outcomes after controlling for potential confounders, including gestational age, mode of delivery, and existing interventions to improve neonatal outcomes of prematurity.Results Of 478 eligible women who delivered singleton very preterm neonates in this study period, 352 (73.6%) used neuraxial analgesia. Women who used neuraxial analgesia were more likely to have delivered at a later preterm gestational age, to have a higher birthweight, to have preeclampsia and/or hemolysis, elevated liver enzymes, low platelet count (HELLP), to have undergone labor induction, to have delivered by cesarean delivery, and to have received obstetric interventions such as magnesium prophylaxis for fetal neuroprotection, antenatal corticosteroids for fetal lung maturity, and antibiotics prior to delivery; they were less likely to have been diagnosed with a clinical abruption. Neuraxial analgesia was associated with decreased incidence of cord umbilical artery pH less than 7.0 (24.7 vs. 34.9%, p = 0.03), as well as decreased incidence of neonatal intensive care unit length of stay over 60 days (35.5 vs. 48.4%, p = 0.01), although these associations did not persist on multivariable analysis. On multivariable analyses, neuraxial analgesia remained independently associated with decreased odds of necrotizing enterocolitis (adjusted odds ratio [aOR]: 0.28, 95% confidence interval [CI]: 0.12–0.62) and grade III/IV intraventricular hemorrhage (aOR: 0.33, 95% CI: 0.13–0.87). These associations remained significant on sensitivity analyses, which were performed between 10 and 90% of the overall cohort in order to control for outliers, as well as between the subgroup of patients who received obstetric interventions.Conclusions Maternal neuraxial analgesia use may be associated with lower odds of adverse outcomes in very preterm infants, even after controlling for existing interventions for prematurity. Prior work has suggested such effects may be due to improved neonatal acid–base status from changes in placental perfusion and maternal pain management, but further work is required to prospectively investigate such associations.
Keywords: neuraxial analgesia; very preterm infants; neonatal outcomes; necrotizing enterocolitis; severe grade intraventricular hemorrhage